2008
DOI: 10.1590/s1516-14392008000300013
|View full text |Cite
|
Sign up to set email alerts
|

LaMn1-xFe xO3 and LaMn0.1-xFe0.90Mo x O3 perovskites: synthesis, characterization and catalytic activity in H2O2 reactions

Abstract: In this work two perovskites were prepared: LaMn 1-x Fe x O 3 , and LaMn 0.1-x Fe 0.90 Mo x O 3 . XRD and Mössbauer spectroscopy suggest the formation of pure phase perovskite with the incorporation of Fe and Mo in the structure. The catalytic activity of these materials was studied in two reactions with H 2 O 2 : the decomposition to O 2 , and the oxidation of the model organic contaminant methylene blue. The perovskite composition strongly affects the catalytic activity, while Fe decreases the H 2 O 2 decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Replacing the element on the A-or B-site in the ABO3 structure, which leads to the change in the composition and symmetry of material, is considered as a promising strategy to improve photocatalytic performance of a catalyst [21][22][23]. Such doping approach could not only…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Replacing the element on the A-or B-site in the ABO3 structure, which leads to the change in the composition and symmetry of material, is considered as a promising strategy to improve photocatalytic performance of a catalyst [21][22][23]. Such doping approach could not only…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…hydrocarbons, chlorinated Volatile Organic Compounds (VOCs) or in the reaction between NO and CO [3,4,5,6]. They are also promising candidates as catalysts in heterogeneous Fenton-like reactions to generate ⋅OH radicals from H 2 O 2 [7,8]. Due to the small band gap LaFeO 3 can be used in photocatalytic applications [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Once again, besides the three samples have shown a very good response for this type of reaction, the samples containing 3 and 6% of vanadium oxide displayed the best discoloration against methylene blue for a 1-hour time, whereas for 90 minutes the 3% sample has the best result. The decomposition of H2O2 promoted by transition metal oxides can lead to the formation of •OH or •OOH radicals, and such radical species are the ones responsible for oxidize all the organic molecules present in the reaction system [23]. Catalytic studies for several different oxidation reactions have demonstrated that the monomeric and polymeric surface VO4 species are generally the catalytic active sites in supported vanadia catalysts, since the crystalline phases possess very few exposed active surface sites, and these sites are the ones responsible for the radical formation.…”
Section: Catalyst Characterizationmentioning
confidence: 99%